Farmers brace for a new round of trade wars - Glauber, Joseph W. (American Enterprise Institute, 2025)
As President-elect Donald Trump prepares to take up residence at the White House for the second time, US farmers nervously await what is in store for the agricultural sector, particularly in trade. In 2018 and 2019, US agriculture suffered from collateral damage during the previous Trump administration as the president’s unilateral actions on trade against foreign suppliers of US imports had serious repercussions for US agricultural exports.